2009
DOI: 10.1071/py08066
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control practices among Aboriginal health professionals in Western Australia

Abstract: Smoking among Aboriginal people is extremely widespread (50 v. 17% of the general population). Aboriginal Health Workers (AHW) are at the vanguard of tackling this problem but many themselves smoke and little is known of their knowledge, attitudes and practices regarding smoking cessation. Structured telephone interviews were conducted with 36 AHW, including 31% current smokers, 31% ex-smokers and 38% non-smokers, to assess their current smoking cessation practices and knowledge of health risks, nicotine depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 2 publications
3
18
0
Order By: Relevance
“…It should be clarified to health professionals that making a referral to the Quitline call‐back service removes cost burden from clients. Another barrier was low client motivation to quit, which is similar to the findings of Pilkington et al 9 This demonstrates the importance of developing a health workforce trained in techniques to build motivation for behaviour change.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It should be clarified to health professionals that making a referral to the Quitline call‐back service removes cost burden from clients. Another barrier was low client motivation to quit, which is similar to the findings of Pilkington et al 9 This demonstrates the importance of developing a health workforce trained in techniques to build motivation for behaviour change.…”
Section: Discussionsupporting
confidence: 80%
“…Health professionals’ provision of cessation interventions may be influenced by beliefs about capabilities to address smoking, 4,5 perceived client receptiveness to intervention, 5,6 beliefs about effectiveness of intervention, 4 and health professional smoking status 6 . High smoking prevalence among health professionals working with Aboriginal and Torres Strait Islander clients has been identified as a barrier to discussing tobacco, 7,8 as has perceiving cessation as a low priority and concern for cultural sensitivities 9 . However, previous studies have not focused upon referrals to Quitline or facilitators for interventions.…”
mentioning
confidence: 99%
“…These factors have previously been highlighted as impeding research involving AHWs [5]. To overcome this difficulty, repeated contact with health services was made to attain up-to-date lists of AHWs.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognised that IHWs are best placed to address tobacco issues in their communities 10 . It is also reported that IHWs are the frontline workers in a critical role to provide health information and education to the community 11 . Therefore it is imperative that IHWs are skilled and confident to deliver tobacco information and/or quit support in order to adequately address very high and persistent rates of smoking.…”
Section: Indigenous Health Workersmentioning
confidence: 99%
“…Some of the peer‐reviewed literature expresses a view that smoking by IHWs is a barrier for them to provide tobacco information and quit support to the community generally and to individual smokers 10–17 . However, the literature providing evidence to supporting this view has not been systematically reviewed.…”
Section: Indigenous Health Workersmentioning
confidence: 99%